Application of Behavioral Architecture in Children Activity Center for Early Childhood - Athira Maisarah; Dwi Lindarto Hadinugroho (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2024)
Behavioral architecture is an essential approach in designing early childhood play spaces. Play is one of their favorite activities and supports social education. However, in Medan City, many playgroups do not support children's play activities regarding space, function, and a sense of safety and comfort for children and parents. Therefore, a building is needed that can accommodate various socially educational play activities for children in Medan City. The proposed children Activity Center with the concept of Behavioral Architecture is designed to provide complete, comfortable, safe, and functional play facilities, as well as spaces that are meticulously adapted to the activities in it, ensuring that children do not feel bored and that the center meets their needs